Molecular filter on-chip design for drug targeting use. (June 2013) - Aziz, M. S.; Jukgoljan, B.; Daud, S.; Tan, T. S.; Ali, J.; Yupapin, P. P.
Abstract This paper presents the use of a modified add/drop optical filter incorporating with microring resonators known as a PANDA microring resonator system which can fabricate on small chip. By using an optical tweezer, the required molecules can be trapped and moved to the required destinations at the add/drop ports. The novelty is that the stored molecules in the designed chip can transport via the optical waveguide and can also be used to form molecular filter, which is an important technique for drug delivery, drug targeting, and molecular electronics. Results have shown that the multivariable filter can be obtained by tunable trapping control.